The Meaning of Color in Lucifer's Character Design in The Sandman (2021) Television Series - Rimbawati, Geugeu; Ekawardhani, Yully Ambarsih (ARTic, 2024)
There are many different depictions of Lucifer, therefore it's intriguing to see if the color representation of Lucifer corresponds with the persona that has been known. Lucifer is an antagonistic character in the television series adapted from Christian mythology. The study uses qualitative research to obtain the meaning of colours in the costumes used by Lucifer's characters followed by its narrative flow. Data is obtained through interviews and literature. This research aims to get the meaning of the colour of the costume used by the character Lucifer in the 2021 television series: The Sandman. The results of the research found that there are three costume colours used, namely, White, Red and Black, from the three colours obtained the meaning of angels, evil, destruction, darkness, death, and anger. the meaning of the colours found can add to and develop knowledge in visual communication design, especially in film, and art. Keyword: Color; Character; Costume; Lucifer; Narratology